MISCO: A Conceptual Model for MIS Implementation in SMEs - R.Bali; G.Cockerham; C.Bloor (Information Research: An International Electronic Journal)
Information Technology ('IT') has made a prolific impact, both in sociological and commercial terms. In the business world, the pursuit of new technology and working practices has often been at the expense of equal regard for the correct methods to manage the new technology. Contemporary IT techniques and methods include Management Information Systems ('MIS') which are normally implemented on a company-wide basis. However, MIS implementation has major cultural and organisational implications which will form the main focus of this paper. A conceptual model is proposed for successful MIS implementation which combines established research findings with ethnographically-informed data from a small, UK-based, business.